Effect of six week sprint and endurance training programs on prepubescent children - Dykstra, G. L.; Demetriou, D. G.; Copay, A. G.; Boileau, R. A. (Medicine & Science in Sports & Exercise, 1996)
Groups (sprint, endurance, and control) of children were trained for 20 minutes in a specific program four times a week for six weeks. No differences were observed between the two training groups in either aerobic or anaerobic performance parameters. Differences were observed between the training a control groups. The training effects of each different program were not specific indicating that children can be trained aerobically in a sprint (anaerobic) program. Implication. The effects of specific training programs are general in children. Any form of training trains all capacities in growing children.